Assessment of building maintenance management practices of higher education institutions in Niger State - Nigeria - Ofide Blessing; Jimoh Richard; Achuenu Emmanuel (Journal of Design and the Built Environment, 2015)
Higher education institutions face immediate pressure to preserve existing building facilities within the campuses and enhance the capacity of their higher education system to address growing demands of an increasing influx of students and academic activities. There is no doubt that dilapidated and unhealthy buildings in a decaying environment depresses the quality of life and contributes in some measure to antisocial behaviours. The buildings of higher education institutions in Nigeria only receive top management attention when there is a problem. Hence, the paper assessed the building maintenance management practices of 6 higher institutions available (2 universities, 2 polytechnics and 2 colleges of education) in Niger State. This was done by interviewing the Directors of Works of the 6 institutions using a structured interview method. The study revealed that there was no maintenance manual in any of the Works Department of the higher education institution, no user satisfaction survey has ever been conducted and none of the institutions had a computerised maintenance management system (CMMS) in place. In addition to these, corrective maintenance was mostly adopted and there was inadequate staffing of the field operatives. All these shortcomings might be responsible for the backlog of maintenance work experienced in the institutions studied. A proactive maintenance system should be put in place, CMMS should be adopted to enhance effective maintenance work, and top management should be enlightened on the imperative of maintenance among other issues competing for funds within the institutions and be more flexible in allocation of resources to enhance maintenance works.